Seasonal Tropopause Dynamics Over Nepal from 2022 to 2023: Insights from GNSS-RO Observations (Journal of Nepal Physical Society, 2024)
Global Navigation and Satellite System-Radio Occultation (GNSS-RO) is the robust method for monitoring the Earth’s atmosphere utilizing the refracted GNSS radio signal. Constellation Observation System for Meteorology, Ionosphere and Climate-2 (COSMIC-2) is one of the GNSS-RO satellite missions providing the bunch of information, which enables us to explore the characteristics of Earth’s atmosphere. It can provide the vertical profile of the atmospheric thermodynamic variable globally with better resolution. The GNSS-RO data features the long-term stability, continuous in all types of weather condition along with very high precision and accuracy. In this pilot project, we are going to study the tropopause dynamics within the periphery of the Nepal, from longitude: 79◦ E to 89◦ E and latitude: 26◦ N to 31◦ N, using the data from COSMIC-2 mission from April 01, 2022 to March 30, 2023, by dividing into four seasons; March-April-May (MAM), June-July-August (JJA), September-October-November (SON) and December-January-February (DJF). For data extraction, we use the netCDF4and Pandas and for the visualization and statistical analysis, we use the Matplotlib, Basemap, Scipy, Scikit-learn, libraries of the Python. The tropopuse height (TRH) and tropopause temperature (TRT) is studied from vertical profile of the temperature using World Meteorological Organization (WMO) and Cold Point (CP) method. The TRH is found maximum in JJA and minimum in MAM in WMO method. In CP method, TRH is obtained maximum in MAM and minimum in SON. The WMO method is best to explain the variation of the TRH along the latitude. However, the CP method is more accurate to the reference data from COSMIC2 compare to the WMO method.